Implementation of Building Information Modeling (BIM) in Sarawak Construction Industry: A Review. Issue 1 (May 2020) - Zaini, N; Ahmad Zaini, A; Tamjehi, S D; Razali, A W; Gui, H C
Abstract: The construction industry believes that Building Information Modeling (BIM) is a platform to transform the construction industry to a higher level by enhancing productivity and efficiency. It is proven that with BIM process execution, productivity can be enhanced through the effective collaboration process, increased return of investment, and reliable information to support the decision-making process. Efficiency can be enhanced through an integrated design process, reliable and accurate cost estimates, reduced financial risk, and reduced potential dispute. Thus, clients are gradually enforcing the use of BIM in their projects, resulting in many construction companies investing in BIM technology to fulfil clients' needs. This paper presents a review of over recent research to identify the key of elements of awareness, benefits, strategies and implementation of BIM. The result reveals that the top ten (10) ranking of BIM awareness, BIM benefits, BIM challenges and BIM strategies for the industry player to implement and adopt BIM in Sarawak construction industry.